Concentrated growth factors for bone regeneration in the distal osseous defect to mandibular second molar after extraction of impacted mandibular third molar: A clinical study - LIANG Yi; KANG Feiwu (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the effect of concentrated growth factors (CGF) in the repair of distal osseous defect to mandibular second molar after extraction of the impacted mandibular third molar, and to compare the clinical efficacy. [Methods:] A total of 25 patients (including 50 extraction sites) whose bilateral impacted mandibular third molars require extraction were recruited. This study was a randomized self‐control clinical trial utilizing a split‐mouth design. After the extraction of mandibular third molars, the ipsilateral side of the extraction site of the same patient was filled with CGF and included in the CGF group, while the contralateral side of the extraction site was not specially treated and included in the control group. Paired t‐test was used to compare the changes in clinical efficacy of osseous defect distal to mandibular second molar between the CGF group and the control group from 1 week to 6 months after the operation. [Results:] At 2 days after operation, the degree of facial swelling in the CGF group was significantly improved compared with that in the control group (P<0.001). At 3 and 6 months after the operation, osseous defect depth (ODD) distal to mandibular second molars of both groups decreased, but ODD change rate and clinical attachment level (CAL) in the CGF group were significantly improved compared with those in the control group (P<0.05). There was no significant difference in the scores of postoperative symptoms severity (PoSSe) scale between the two groups. [Conclusion:] This study reveals that CGF would be beneficial to improve facial swelling of patients, favoring bone formation and affecting bone remodeling in the distal aspect of mandibular second molars after extraction of impacted mandibular third molars.